A crítica de Rousseau à sociedade: a vida pública como espetáculo - Scholz, Caio Cezar Pontim (2017)
The study of Rousseau´s philosophical thought, in a contemporary context, allows an interpretation of his work under two distinct aspects. The first one of them tells about the comprehension of its conceptual display, that substantiate its notorious critic potential, which the target is found in the fields of the ethics and the politics, references to the exercise of the public life, understood as form of spectacle, belonging to the modern social organization. The second one provokes the sensation of its critics and conceptual display, somehow, continue actual and can contribute to the comprehension of the spectacle of the public life, demonstrated in the contemporary society. In front of that scenario, when investigating those two possibilities of interpretation, will be shown that some elements of Rousseau´s work are kept in the contemporaneity, others seem to gain a sort of present time according to that contemporary social context and, lastly, some difficulties seem to be overcome due to specificities belonging only to the contemporary society. To accomplish such assumption, the first two chapters will be dedicated to the detailed study of the work of Rousseau, that will serve as the foundation to, in the third, delimit a contemporary social scenario and investigate it to the light of Rousseau.